Metabolic Adaptations of White Lupin Roots and Shoots under Phosphorus Deficiency - Müller, Julia; Gödde, Victoria; Niehaus, Karsten; Zörb, Christian (Frontiers in Plant Science, 2015)
White lupin (Lupinus albus L.) is highly adapted to phosphorus-diminished soils. P-deficient white lupin plants modify their root architecture and physiology to acquire sparingly available soil phosphorus. We employed gas chromatography–mass spectrometry (GC MS) for metabolic profiling of P-deficient white lupins, to investigate biochemical pathways involved in the P-acquiring strategy. After 14 days of P-deficiency, plants showed reduced levels of fructose, glucose and sucrose in shoots. Phosphorylated metabolites such as glucose-6-phosphate, fructose-6-phosphate, myo-inositol-phosphate and glycerol-3-phosphate were reduced in both shoots and roots. After 22 days of P-deficiency, no effect on shoot or root sugar metabolite levels was found, but the levels of phosphorylated metabolites were further reduced. Organic acids, amino acids and several shikimate pathway products showed enhanced levels in 22-day-old P-deficient roots and shoots. These results indicate that P-deficient white lupins adapt their carbohydrate partitioning between shoot and root in order to supply their growing root system as an early response to P-deficiency. Organic acids are released into the rhizosphere to mobilize phosphorus from soil particles. A longer period of P-deficiency leads to scavenging of Pi from P-containing metabolites and reduced protein anabolism, but enhanced formation of secondary metabolites. The latter can serve as stress protection molecules or actively acquire phosphorus from the soil.